Chloroquine Versus Dihydroartemisinin-Piperaquine With Standard High-dose Primaquine Given Either for 7 Days or 14 Days in Plasmodium vivax Malaria - Chu, Cindy S (Clin Infect Dis, 2019)
BACKGROUND: Primaquine is necessary for the radical cure of Plasmodium vivax malaria, but the optimum duration of treatment and best partner drug are uncertain. A randomized controlled trial was performed to compare the tolerability and radical curative efficacy of 7-day versus 14-day high-dose primaquine regimens (total dose 7mg/kg) with either chloroquine or dihydroartemisinin-piperaquine. METHODS: Patients with uncomplicated P. vivax malaria on the Thailand-Myanmar border were randomized to either chloroquine (25mg base/kg) or dihydroartemisinin-piperaquine (dihydroartemisinin 7mg/kg and piperaquine 55mg/kg) plus primaquine, either 0.5 mg/kg/day for 14 days or 1 mg/kg/day for 7 days. Adverse events within 42 days and 1-year recurrence rates were compared and their relationship with day 6 drug concentrations assessed. RESULTS: Between February 2012 and July 2014, 680 patients were enrolled. P. vivax recurrences (all after day 35) occurred in 80/654 (12%) patients; there was no difference between treatments. Compared to the 7-day primaquine groups the pooled relative risk of recurrence in the 14-day groups was 1.15 (95% confidence interval 0.7 to 1.8). Hematocrit reductions were clinically insignificant except in G6PD female heterozygotes, 2 of whom had hematocrit reductions to <23% requiring blood transfusion. CONCLUSION: Radical cure should be deployed more widely. The radical curative efficacy in vivax malaria of 7-day high-dose primaquine is similar to the standard 14-day high-dose regimen. Chloroquine and dihydroartemisinin-piperaquine are both highly effective treatments of the blood stage infection. Quantitative point of care G6PD testing would ensure safe use of the 7-day high-dose primaquine regimen in G6PD heterozygous females. CLINICAL TRIALS REGISTRATION: NCT01640574.